Novel screening criteria for post‐traumatic venous thromboembolism by using D‐dimer. Issue 1 (17th October 2018) - Iyama, Keita; Inokuma, Takamitsu; Sato, Shuntaro; Yamano, Shuhei; Tajima, Goro; Hirao, Tomohito; Tasaki, Osamu
Abstract : Aim: Because severe trauma patients frequently manifest coagulopathy, it is extremely important to detect venous thromboembolism (VTE) in the acute phase. However, no reference value for D‐dimer in post‐traumatic VTE has been reported given the substantial increase in its levels after injury. Therefore, this study evaluates the ability of our screening criteria using D‐dimer to detect VTE in severe trauma patients. Methods: Trauma patients ( n  = 455) who were admitted to our emergency medical center during October 2011–June 2015 were included in this study. To prevent VTE, intermittent pneumatic compression was carried out in most patients. Our screening criteria included the following: (i) ≥5 days of hospital stay, (ii) increasing D‐dimer levels across 3 measuring days, (iii) D‐dimer levels ≥15 μg/mL. Patients who met these screening criteria underwent contrast‐enhanced computed tomography (CE‐CT) to detect VTE. Results: During the study period, 108 cases satisfied the screening criteria; 73 of these underwent CE‐CT, 34 of whom were diagnosed with VTE (positive predictive value, 46.6%). The median hospital stay on satisfying the screening criteria and before undergoing CE‐CT was 7 and 10 days, respectively. No patient had VTE symptoms at the time of diagnosis. Also, none of the remaining 347 patients who did not satisfy the screening criteria had VTE symptoms. Conclusion: The screening criteria using D‐dimer presented herein can be used as reference for efficiently detecting VTE in severe trauma patients. Abstract : Asymptomatic venous thromboembolism (VTE) after trauma could be detected using the following screening criteria: (i) ≥5 days of hospital stay, (ii) increasing D‐dimer levels across 3 measuring days, (iii) D‐dimer levels ≥15 μg/mL. Additionally, symptomatic VTE development had not been observed in all cases, including those that did not satisfy these screening criteria. Therefore, the criteria presented herein can serve as a reference for establishing routine practices that efficiently detect VTE after trauma.